2020
DOI: 10.1002/lary.28514
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience of Vibroplasty With Direct Coupling to the Oval Window Without Use of a Coupler

Abstract: Objectives/Hypothesis: To investigate the efficacy of direct implantation of a Vibrant Soundbridge (VSB) implant in the oval window (OW) without the use of an OW coupler in patients with severe mixed hearing loss. Study Design: Retrospective chart review. Methods: A total of 62 patients underwent VSB implantation between July 2016 and December 2018 at Severance Hospital in Seoul, South Korea. Among them, eight patients (nine ears) with moderate-to-severe mixed hearing loss were implanted with a VSB directly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…When direct- and cartilage-AC are not functional, patients who receive the most benefits from CC-HAs are patients with aural atresia. These patients require BC-HAs or implantable devices to achieve sufficient amplification [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, conventional BC-HAs have disadvantages associated with their fixation style; the transducer is fixed with a headband using static force, which can lead to discomfort, pain, and irritation [ 26 ].…”
Section: CC Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When direct- and cartilage-AC are not functional, patients who receive the most benefits from CC-HAs are patients with aural atresia. These patients require BC-HAs or implantable devices to achieve sufficient amplification [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, conventional BC-HAs have disadvantages associated with their fixation style; the transducer is fixed with a headband using static force, which can lead to discomfort, pain, and irritation [ 26 ].…”
Section: CC Applicationsmentioning
confidence: 99%
“…The fixation of the transducer can cause poor esthetics. Surgical procedures, such as implanting bone-anchored hearing aids (BAHAs), are additional options [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ] but involve various risks, such as adverse medical and surgical events, infection, and follow-up surgery [ 32 , 33 ]. Some patients also refuse BAHA implantation because of cosmetic considerations [ 34 ].…”
Section: CC Applicationsmentioning
confidence: 99%
“…Zehlicke et al (14) reported results of seven cases after direct OW vibroplasty finding a similar mean FHG with decreased aided speech discrimination in comparison to our data. More recently Kwak et al (33) reported a better FHG of around 44 dB after direct OW vibroplasty and furthermore observed an improvement of passive sound transmission in four cases.…”
Section: Discussionmentioning
confidence: 87%
“…Fortunately, the enrolled patients were satisfied with their CC‐HAs and continued to use them. When CC‐HAs cannot sufficiently compensate for hearing loss because of limitations of the output levels, other options, such as BAHA, Bonebridge, VSB, Osia, Ponto, and Alpha 2MPO, 22 , 34 , 35 , 36 , 37 have to be considered.…”
Section: Discussionmentioning
confidence: 99%